Identification of oxidative stress-related genes and potential mechanisms in atherosclerosis - Tang, Chao; Deng, Lingchen; Luo, Qiang; He, Guijun (Frontiers in Genetics, 2023)
Atherosclerosis (AS) is the main cause of death in individuals with cardiovascular and cerebrovascular diseases. A growing body of evidence suggests that oxidative stress plays an essential role in AS pathology. The aim of this study was to determine the mechanisms associated with AS and oxidative stress. Seventeen oxidative stress-related genes were identified. A four-gene (ALDH6A1, EEF2K, GLRX, and LDHB) diagnostic model was constructed using the least absolute shrinkage and selection operator (LASSO) algorithm based on these 17 genes. The area under the Receiver Operating Characteristic (ROC) curve (AUC) was 0.967. Based on the GO analysis, cell-substrate adherens junction and focal adhesion were the most enriched terms. KEGG analysis revealed that these overlapping genes were enriched in pathways associated with Alzheimer’s disease and Parkinson’s disease, as well as with prion disease pathways and ribosomes. Immune cell infiltration correlation analysis showed that the immune cells with significant differences were CD4 memory activated T cells and follicular helper T cells in the GSE43292 dataset and CD4 naïve T cells and CD4 memory resting T cells in the GSE57691 dataset. We identified 17 hub genes that were closely associated with oxidative stress in AS and constructed a four-gene (ALDH6A1, EEF2K, GLRX, and LDHB) diagnostic model with good accuracy. The four-gene diagnostic model was also found to have good discriminatory efficacy for the immune cell infiltration microenvironment of AS. Overall, these findings provide valuable information and directions for future research into AS diagnosis and aid in the discovery of biological mechanisms underlying AS with oxidative stress.